TRANSFORMASI DIRI BERDASARKAN FILSAFAT JIWA IBN SĪNĀ - Saleh Saleh; Humaidi Humaidi (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2022)
This research is motivated by the weakness of the existing self-transformation methods. Whereas self-transformation is part of management science which is very important in helping companies and knowing the process of change in humans. Even so, the presence of various methods of self-transformation is still felt to be a weakness—especially the need for external influence from the self. In fact, self-transformation should also be driven by awareness in humans. By using descriptive qualitative analysis method, it is found that self-transformation can be seen from the point of view of Ibnu Sīnā 's philosophy of the soul which directs the soul to be completely transformed. Although there is no explicit discussion of Ibnu Sīnā 's theory of self-transformation, Ibnu Sīnā 's formulation of self-transformation theory is better than Aristotle's implicitly and provides an alternative method of self-transformation.